26Al‐26Mg isotope systematics of the first solids in the early solar system. (19th July 2013) - Kita, Noriko T.; Yin, Qing‐Zhu; MacPherson, Glenn J.; Ushikubo, Takayuki; Jacobsen, Benjamin; Nagashima, Kazuhide; Kurahashi, Erika; Krot, Alexander N.; Jacobsen, Stein B.
Abstract High‐precision bulk aluminum‐magnesium isotope measurements of calcium‐aluminum‐rich inclusions (CAIs) from CV carbonaceous chondrites in several laboratories define a bulk 26Al‐26Mg isochron with an inferred initial 26Al/27Al ratio of approximately 5.25 × 10−5, named the canonical ratio. Nonigneous CV CAIs yield well‐defined internal 26Al‐26Mg isochrons consistent with the canonical value. These observations indicate that the canonical 26Al/27Al ratio records initial Al/Mg fractionation by evaporation and condensation in the CV CAI‐forming region. The internal isochrons of igneous CV CAIs show a range of inferred initial 26Al/27Al ratios, (4.2–5.2) × 10−5, indicating that CAI melting continued for at least 0.2 Ma after formation of their precursors. A similar range of initial 26Al/27Al ratios is also obtained from the internal isochrons of many CAIs (igneous and nonigneous) in other groups of carbonaceous chondrites. Some CAIs and refractory grains (corundum and hibonite) from unmetamorphosed or weakly metamorphosed chondrites, including CVs, are significantly depleted in 26Al. At least some of these refractory objects may have formed prior to injection of 26Al into the protosolar molecular cloud and its subsequent homogenization in the protoplanetary disk. Bulk aluminum and magnesium‐isotope measurements of various types of chondrites plot along the bulk CV CAI isochron, suggesting homogeneous distribution of 26Al and magnesium isotopes in the protoplanetary disk after an epoch of CAI formation. The inferred initial 26Al/27Al ratios of chondrules indicate that most chondrules formed 1–3 Ma after CAIs with the canonical 26Al/27Al ratio.